Field Tests on Total Gap of Modular Expansion Joints to Avoid Bridge Pounding - Li, Bo; Chouw, Nawawi (Frontiers in Built Environment, 2016)
Modular expansion joints (MEJs) are used for accommodating large relative displacements of adjacent bridge segments and for completely eliminating pounding. However, the minimum total gap that an MEJ needs to avoid pounding is not well investigated. To provide guidance for the seismic gap of MEJs, the maximum relative displacement of adjacent bridge segments subject to strong earthquakes was studied experimentally. To date, no experimental investigation of excitation spatial variation effect on bridge on natural soil has been reported. This research addressed a bridge with three identical segments of 100 m. A 1:22 scale bridge model founded on compacted beach sand was tested using electro-magnetic inertial exciters. Different ground motions were applied to the model to simulate the effect of spatially varying ground motions. Soil-structure interaction (SSI) was studied by comparing the minimum total gaps with those obtained from the fixed-based experiments in the laboratory. The spatially varying ground motions were simulated based on the New Zealand design spectra for soft soil, shallow soil and strong rock conditions using an empirical coherency loss function. SSI was found to reduce the minimum total gap of an MEJ needed to avoid pounding between adjacent segments. Under spatially varying ground motions designing adjacent bridge segments with identical or similar fundamental frequencies is still recommended even if it does not necessarily preclude an out-of-phase movement of adjacent structures.